2018
DOI: 10.1016/j.plaphy.2017.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the WUSCHEL-RELATED HOMEOBOX gene family in Pinus pinaster : New insights into the gene family evolution

Abstract: WUSCHEL-RELATED HOMEOBOX (WOX) genes are key players controlling stem cells in plants and can be divided into three clades according to the time of their appearance during plant evolution. Our knowledge of stem cell function in vascular plants other than angiosperms is limited, they separated from gymnosperms ca 300 million years ago and their patterning during embryogenesis differs significantly. For this reason, we have used the model gymnosperm Pinus pinaster to identify WOX genes and perform a thorough ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 72 publications
5
49
0
Order By: Relevance
“…In contrast, WOX2 expression was detected in both embryogenic and non-embryogenic lines in P. radiata , although transcript levels were lower in the latter (Bravo et al, 2017). Maritime pine WOX gene family has been studied recently (Alvarez et al, 2018) and WOX2 expression has been shown to be highest at early embryogenic stages and decreased along the maturation process being lower in mature somatic embryos which agree with our WOX2 expression profile sampled at 0, 7, and 12 weeks in SK lines. Similar results were obtained in other conifers as Pinus sylvestris (Merino et al, 2018), Picea (Palovaara and Hakman, 2008; Klimaszewska et al, 2011), Larix decidua (Rupps et al, 2016), Pinus contorta (Park et al, 2010), and Chinese fir (Zhou et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, WOX2 expression was detected in both embryogenic and non-embryogenic lines in P. radiata , although transcript levels were lower in the latter (Bravo et al, 2017). Maritime pine WOX gene family has been studied recently (Alvarez et al, 2018) and WOX2 expression has been shown to be highest at early embryogenic stages and decreased along the maturation process being lower in mature somatic embryos which agree with our WOX2 expression profile sampled at 0, 7, and 12 weeks in SK lines. Similar results were obtained in other conifers as Pinus sylvestris (Merino et al, 2018), Picea (Palovaara and Hakman, 2008; Klimaszewska et al, 2011), Larix decidua (Rupps et al, 2016), Pinus contorta (Park et al, 2010), and Chinese fir (Zhou et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…However, studies on some of the genes associated with conifer embryogenesis as LEAFY COTYLEDON ( LEC1 ), WUSCHEL-related HOMEOBOX2 ( WOX2 ) and SOMATIC EMBRYOGENESIS RECEPTOR-like KINASE ( SERK ) demonstrated that the expression of these genes varied along embryogenesis and are differentially expressed in embryogenic and non-embryogenic cultures in some species (Yang and Zhang, 2010; Klimaszewska et al, 2016). Recently, Alvarez et al (2018) reported on the characterization of the WUSCHEL-RELATED HOMEOBOX gene family in maritime pine and its expression during SE.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PpWOX5, which is orthologous to AtWOX5, shows maximum expression at the mature-embryo stage, with transcripts preferentially located to the root tip of seedlings. This, in combination with low expression levels in other seedling tissues, mirrors the expression pattern of AtWOX5, which has been shown to influence stem-cell function in Arabidopsis RAM (Alvarez et al 2017).…”
Section: Embryonic Wox Expression In Coniferssupporting
confidence: 53%
“…Alvarez et al () recently reported high expression of two Pinus pinaster WOX genes, both of which are closely related to AtWOX9 , in early and late embryos, with expression decreasing dramatically in germinated embryos. In addition, PpWOX5 , which is orthologous to AtWOX5 , shows maximum expression at the mature‐embryo stage, with transcripts preferentially located to the root tip of seedlings.…”
Section: Embryonic Wox Expression In Conifersmentioning
confidence: 99%
“…Among these CYCs, A-and B-type CYCs regulate the cell cycle progression through the S-, G2-and early M-phase, while D-type CYCs regulate the cell cycle progression of G1/S phase transition (Nafati et al 2010). The plantspecific homeobox transcription factor WUSCHELrelated homeobox (WOX) gene family plays vital roles in modulating plant growth and development by controlling stem cell activity in shoot/root apical meristem and cambium (Alvarez et al 2018, Li et al 2019.…”
Section: Introductionmentioning
confidence: 99%